Personality traits and Management practices of administrators from selected public elementary schools, Division of Laguna: 1998-1999 - Magpantay, Dionisia B. (Manila : National University, 1999)
This study was conducted in selected elementary schools in the Division of Laguna. The research was primarily concerned in assessing the personality traits and skills of administrators in selected public elementary schools.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Design: Descriptive Method.
Includes bibliographical references.